Jezik kot kazalec stanja medetničnih odnosov - Nećak Lük, Albina (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1996)
The research study on interethnic relations and ethnic identity in the Slovene ethnic territory highlights the sociolinguistic aspect of the situation in the three ethnically mixed regions, i.e. relations between ethnic affiliation and mother tongue, communicative competence, communicative activity as well as language attitudes of the minority and majority members participating in the research.
Keywords: jezik; mednacionalni odnosi; narodna identiteta; narodnostno mešana območja; raba jezika; Slovenija; sociolingvistika